Co Nanoparticles Encapsulated in Porous N-Doped Carbon Nanofibers as an Efficient Electrocatalyst for Hydrogen Evolution Reaction. Issue 15 (26th October 2018) - Zhang, Lulu; Zhu, Shangqian; Dong, Shuyu; Woo, Nam Jae; Xu, Zhenglong; Huang, Jiaqiang; Kim, Jang-Kyo; Shao, Minhua
Abstract : One of the main challenges in commercializing electrolyzer is to develop cheap and highly active electrocatalysts toward hydrogen evolution reaction (HER). Although low Pt loadings in PEM electrolyzers have been demonstrated, it's still worthwhile to remove the Pt in the long term. Herein, porous N-doped carbon nanofibers containing encapsulated Co nanoparticles are in situ obtained by electrospinning and subsequent carbonization as efficient electrocatalysts for HER. The optimized catalyst treated at 800°C shows a remarkably high HER activity with an overpotential of only 159 mV at current density of 10 mA cm −2 in a 0.5 M H2 SO4 solution, which is better than most non-precious metal based and metal free catalysts. The carbonization temperature as well as the concentration of nitrogen precursors have significant effects on the structure and catalytic activity of the composites. This work shows the efficacy of preparing noble-metal-free electrocatalysts for HER using the facile electrospinning method.